2022
DOI: 10.3390/en15196975
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Mechanism of Tourism Carbon Emission Efficiency and Tourism Economy High-Quality Development in the Yellow River Basin

Abstract: Exploring the relationship between the tourism carbon environment and high-quality economic development in the Yellow River Basin is a national strategy to meet the realistic requirements of the goal of “Carbon Peak and Carbon Neutral”. It is also conducive to the realization of “Ecological Protection and High-quality Development Strategy in the Yellow River Basin”. Therefore, based on the calculation of tourism’s carbon emission efficiency and the evaluation of the tourism economy’s high-quality development, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Xiong et al 57 discovered that there is a feeble decoupling linkage between the regional TCDE and the economic progress, which is primarily driven by tourism in China. As the pursuit of high-quality development of TE continues, the growth rate of TE is likely to remain higher than the growth rate of TCDE, leading to an even wider gap in their respective growth rates 58 . When the second half of the inverted U-shaped relation of EKC appears, the decrease of TCDE and CD may lead to the decrease of CCD.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong et al 57 discovered that there is a feeble decoupling linkage between the regional TCDE and the economic progress, which is primarily driven by tourism in China. As the pursuit of high-quality development of TE continues, the growth rate of TE is likely to remain higher than the growth rate of TCDE, leading to an even wider gap in their respective growth rates 58 . When the second half of the inverted U-shaped relation of EKC appears, the decrease of TCDE and CD may lead to the decrease of CCD.…”
Section: Discussionmentioning
confidence: 99%
“…The new development concept to construct an evaluation system for the high-quality development level of tourism has received widespread attention from Chinese scholars. The five dimensions of "innovation, coordination, green, openness and sharing" measure the level of quality tourism development at national [25], basin [26,27], and inter-provincial levels [28], respectively, proving that the overall level of tourism in China is on the rise. The study found that technological innovation in tourism [29] and the promotion of renewable energy [30] can significantly improve carbon efficiency.…”
Section: The Level Of High-quality Development Of Tourismmentioning
confidence: 99%
“…For example, from the supply side perspective, He et al (2023) [15] constructed a high-quality tourism evaluation system including five dimensions of tourism economic scale, development speed, supply quality, industrial tourism structure, and tourism industry benefits. Drawing on the new development philosophy, [23] constructed an evaluation index system of the tourism economy's high-quality development from five dimensions: innovation, coordination, green, openness, and sharing. Lu (2022) [16] measured the high-quality development level of tourism from the four dimensions of the tourism industry economy, structure, integration, and performance.…”
Section: High-quality Development Of Tourismmentioning
confidence: 99%
“…AT is the impact of all-for-one tourism demonstration zones in the treatment group. 2022) [23] and Chen and Huo (2022) [38], this research constructs a five-dimension indicator system to explain the affluent connotation of high-quality tourism development under the instruction of the new development philosophy.…”
Section: Model Designmentioning
confidence: 99%